Redescription of the type specimens of Althepus pictus Thorell, 1898 (Araneae, Psilodercidae) from Myanmar - Lin, Yejie; Tavano, Maria L.; Li, Shuqiang; Chen, Haifeng (Zootaxa, 2020)
Althepus pictus Thorell, 1898 is the type species of the genus Althepus Thorell, 1898 from the family Psilodercidae Machado, 1951. This genus includes 60 species from Southeast Asia (WSC 2020). A. pictus was described on the basis of one male and one female from Carin Chebà mountains, elevation 600‒800 m, Kayin Province, Myanmar. Another female specimen lacking several legs was found in Farm Caves in Mawlamyine, Mon State, Myanmar. The original description was in Latin and without any figures. Fage (1912) redescribed it based on the same male and female type specimens from Carin Chebà, but without mentioning the female from Farm Caves. Fage (1912) provided measurements, but the figures of the male right palp are imprecise. The species is redescribed here based on the original male and female type specimens deposited in Museo Civico di Storia Naturale ‘Giacomo Doria’ (MSNG) in Italy. The male and female type specimens are the only known material of A. pictus. No information is available on the female specimen from Farm Caves, which maybe have been lost. No fresh material of this species has been collected in region during five subsequent expeditions to Myanmar tours organized by the Southeast Asia Biodiversity Research Institute in the years 2016–2020.